Review of recent experimental and modeling advances in the understanding of lower hybrid current drive in ITER-relevant regimes. (20th July 2018) - Ding, B.J.; Bonoli, P.T.; Tuccillo, A.; Goniche, M.; Kirov, K.; Li, M.; Li, Y.; Cesario, R.; Peysson, Y.; Ekedahl, A.; Amicucci, L.; Baek, S.; et al.
Abstract: Progress in understanding lower hybrid current drive (LHCD) at high density has been made through experiments and modeling, which is encouraging given the need for an efficient off-axis current profile control technique in burning plasma. By reducing the wall recycling of neutrals, the edge temperature is increased and the effect of parametric instability (PI) and collisional absorption (CA) is reduced, which is beneficial for increasing the current drive efficiency. Strong single pass absorption is preferred to prevent CA and high LH operating frequency is essential for wave propagation to the core region at high density, presumably to mitigate the effect of PI. The dimensionless parameter that characterizes LH wave accessibility and wave refraction for the experiments in this joint study is shown to bracket the region in parameter space where ITER LHCD experiments will operate in the steady state scenario phase. Further joint experiments and cross modeling are necessary to understand the LHCD physics in weak damping regimes which would increase confidence in predictions for ITER where the absorption is expected to be strong.